1997
DOI: 10.1136/gut.40.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors of recurrent pain during refeeding in patients with acute pancreatitis: a multivariate multicentre prospective study of 116 patients.

Abstract: Background/Aims-The period of refeeding in patients with acute pancreatitis is critical because they may have pain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 5 publications
6
56
0
5
Order By: Relevance
“…Fourteen of 17 publications were subsequently excluded because they were guidelines, editorials, or studies in which the outcome variables were not reported. A total of three trials were included in the review (8)(9)(10). The characteristics of included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen of 17 publications were subsequently excluded because they were guidelines, editorials, or studies in which the outcome variables were not reported. A total of three trials were included in the review (8)(9)(10). The characteristics of included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Because patients with pain relapse tended to have a longer duration of initial abdominal pain (10), persistent elevation of serum enzymes (10), and higher Balthazar's scores on admission (8,9), it may well be that patients with pain relapse are those with more severe acute pancreatitis (11). However, due to the significantly longer postrefeeding length of hospital stay (8,9) and the absence of difference in the severity scores between patients with and without pain relapse (8)(9)(10), premature oral refeeding could also be responsible for the pain relapse. Refeeding pain may be caused by restimulation of pancreatic secretion by oral bolus feeding, which may activate both dormant enzymes and the inflammatory process (12).…”
Section: Discussionmentioning
confidence: 99%
“…Petrov [17] pointed out in Moraes study that the rate of feeding intolerance was around 20%, regardless of the type of initial diet used for oral refeeding and this was unacceptable both from the perspective of patient's quality of life and the cost of treatment. However, this rate of intolerance was observed also in other trials [5,6] and it seems a rule in oral refeeding of patients with mild AP.…”
Section: Refeeding In Apmentioning
confidence: 89%
“…In 1997, Lévy et al [5] , in a multivariate multicenter prospective study, tried to analyze the frequency and risk factors of recurrent pain during oral refeeding in 116 patients with mild AP. The conclusion was that pain relapse occurred in 20% of the patients and was more common in patients with necrotizing pancreatitis who had longer periods of pain.…”
Section: Refeeding In Apmentioning
confidence: 99%
“…Bei Patienten mit nekrotisierender Pankreatitis siedeln sich die translozierten Bakterien bevorzugt in der Pankreasnekrose an und können eine der gefürchtetsten Komplikationen der Pankreatitis -die infizierte Nekrose oder den Pankreasabszess verursachen. Eine enterale Sondenernäh-rung, die über eine tief liegende Dünndarmsonde oder, nach neuesten Studien, mit gleicher Effektivität auch über eine Magensonde verabreicht wird, wirkt der Translokation entgegen und hat sich als Alternative zur parenteralen Ernährung bewährt [194 -197] Schweregrad der Pankreatitis, abhängig ist [199]. Eine Metaanalyse, die alle 3 der hierzu publizierten Studien einschließt (274 Patienten), bestätigt dieses Ergebnis [200].…”
Section: Leitlinie 1187unclassified